Psoralen Isolated from the Roots of Dorstenia psilurus Welw. Modulate Th1/Th2 Cytokines and Inflammatory Enzymes in LPS-Stimulated RAW 264.7 Macrophages - Adamu Imam Isa; Hugues Fouotsa; Osama A. Mohammed; Mushabab Alghamdi; Bappa Adamu; Jaber Alfaifi; Abubakar Mohammed Jibo; Mohannad Mohammed Saleh Alamri; Sameer Khan; Masoud Ishag Elkhalifa Adam; Abdullah Ali Alqarni; Mohamed O'haj Mohamed; et al. (Hindawi Limited, 2024)
Dorstenia psilurus is a widely used plant spice in traditional African medicine to treat pain-related conditions. However, the anti-inflammatory mechanisms underlying this activity and the main active ingredients of D. psilurus have not yet been fully characterized. This study aimed to isolate and identify the main active anti-inflammatory constituents of the D. psilurus extract and to investigate the underlying anti-inflammatory mechanisms in murine macrophages. Chromatographic techniques and spectroscopic data were used for compound isolation and structure elucidation. The Griess reagent method and the ferrous oxidation-xylenol orange assay were used to evaluate the inhibition of NO production and 15-lipoxygenase activity, respectively. Cyclooxygenase activity was assessed using the fluorometric COX activity assay kit, and Th1/Th2 cytokine measurement was performed using a flow cytometer. The results indicated that the extract and fractions of D. psilurus inhibit NO production and proliferation of RAW 264.7 macrophage cells. Bioguided fractionation led to the identification of psoralen, a furocoumarin, as the main bioactive anti-inflammatory compound. Psoralen inhibited NO production and 15-lipoxygenase activity and reduced pro-inflammatory Th1 cytokines (IFN-γ, TNF-α, and IL-2) while increasing the secretion of anti-inflammatory cytokines (IL-4, IL-6, and IL-10) in activated RAW 264.7 macrophage cells. The encouraging results obtained in this study suggest that psoralen-based multiple modulation strategies could be a useful approach to address the treatment of inflammatory diseases.